Educational and Socio-cultural Factors Influencing the Growth of Entrepreneurial Activities in Khartoum State, Sudan - Timan, Elfadil; Babiker, Yusra. H. M.; Ali, Malik Elnaeem Mohammed (Research in Business and Management, 2023)
The goal of this article is to explore the educational and socio-cultural factors which influence the growth of entrepreneurial activities in Khartoum locality, Khartoum State, Sudan. The research was conducted on a sample of 400 national potential entrepreneurs, and data were collected using a structured questionnaire and personal interviews. Respondents are asked 43 questions to assess their perception of the main factors influencing the growth of entrepreneurial activities. The study adopted an analytical descriptive methodology whereby the data were processed by the statistical package for social sciences (SPSS). Percentages, frequencies, and hypothesis tests were used to analyze data. The study revealed that it’s important for entrepreneurs to have the necessary knowledge, entrepreneurial potential, skills, and creative ideas in turn to contribute to the development of entrepreneurial activities. Also, entrepreneurs must have administrative practical, and technical capabilities in their field. Entrepreneurship culture should be included in the academic curricula of universities. Entrepreneurial activities must be consistent with the values and beliefs of the community members because the spread of entrepreneurial culture among community members contributes to the development of entrepreneurial activities. The study recommends that there must be educational institutions that provide the necessary information the entrepreneurs need and that entrepreneurship should be included in universities’ curricula. Spreading the culture of entrepreneurship among community members through training workshops, training courses and the media in general will enhance entrepreneurial activities. When considering entrepreneurship training it is important to put into account the influence of religious beliefs and tribal differences between society components which may affect entrepreneurial activities.